Phosphorus and Zinc Interaction Influence Leaf Area Index in Fine vs. Coarse Rice (Oryza sativa L) Genotypes in Northwest Pakistan - ,, Amanullah; ,, Inamullah; Shah, Zahir; Khan Khalil, Shad (Journal of Plant Stress Physiology, 2016)
Leaf area index (LAI) is a measure of leafiness per unit ground area and denotes the extent of photosynthetic machinery is an important growth and yield-determining factor because it is a major determinant of light interception and transpiration. Phosphorus (P) and zinc (Zn) and rate are the most important factors affecting leaf area index (LAI) of rice(Oryza sativa L.). A field experiment was conducted to assess the impact of phosphorus (0, 40, 80, 120 kg P ha-1) and zinc levels (0, 5, 10, 15 kg Zn ha-1) on LAI of rice (Oryza sativa L.) genotypes [fine (Basmati-385) and coarse (Fakhr-e-Malakand & Pukhraj)]. The experiment was conducted on farmer field at Batkhela, Malakadnd in Northwest Pakistan during summer 2011 and 2012. When combined over the two years, the data revealed that the highest LAI at three different growth stages (tillering, heading and physiological maturity) was obtained with application of the highest P level (120 kg ha-1) being at par with 80 kg P ha-1, while the lowest LAI was recorded when P was not applied. Similarly, the highest LAI was obtained with application of the two higher Zn levels (10 and 15 kg Zn ha-1), while the lowest LAI was recorded when Zn was not applied. In case of rice genotypes, the highest LAI was obtained from Pukhraj than other two genotypes at all growth stages. The other two rice genotypes (Fakher-e-Malakand and Basmati-385) produced statistically similar LAI at different growth stages. The higher LAI of Pukhraj was attributed to its long and wider leaves that resulted in higher mean single leaf area, leaf area per tiller, per hill and per square meter. The LAI was highest at heading stages than at early (tillering) and later (physiological maturity) growth stages. The increase in LAI was attributed to the increase in tillers number and leaf area hill-1. The increase in LAI showed positive impact on crop growth rate, dry matter accumulationand yield. Application of 120 kg P + 10 kg Zn ha-1 to rice genotype Pukhraj was more beneficial in terms of higher LAI and productivity in the study area.